Mediating Role of Self-efficacy to Sustain Women Entrepreneurship in Nepal - Ghimire, Radha Devi (The Batuk, 2024)
Self-efficacy in terms of entrepreneurship is the perceived ability of entrepreneurs to overcome the special situations faced during the business operation. This study has been carried out to examine the mediating role of self-efficacy between policy support and sustainable women entrepreneurship in Nepal. Women having at least three years of business experience were selected from four provinces that are convenient to the researcher. A total of 353 survey questionnaires were collected from the sample. Casual relational research design was used to find the effect of policy support and self-efficacy on the survivability of women’s businesses. Structural equation modeling with AMOS was used to analyze the five-point Likert scale structured questionnaire. The result found that policy support has a significant indirect effect on entrepreneurial survivability through the mediating effect of self-efficacy. In the presence of the mediating variable, policy support has a non-significant direct relationship to survivability. This means the influence of policy support on survivability is fully mediated through the mediation of self-efficacy. This study suggests the policy makers to emphasize self-efficacy while making intervention plan regarding the promotion of women entrepreneurship and their business sustainability in Nepal.